Fluorescence-aided caries excavation – preliminary own report - Chałas, Renata; Janczarek, Magdalena; Cieszko-Buk, Maria; Sobieszczański, Jarosław; Bachanek, Teresa (Journal of Stomatology, 2015)
Introduction. The removal of infected dentine is a key step allowing the successful restorative treatment and infection prevention. FACE technique involves directing the ray of ultraviolet light to the bottom of the cavity and inducing autofluorescence of the examined tissues. While working with the device, the operator can immediately assess the level of caries development without previous staining, and can obtain “visual tint” of healthy tissues in green and red in the case of infected dentine. Aim of the study. To evaluate the clinical use of Facelight, as well as its utility in everyday dental practice during cavity preparation. Material and methods. The study was conducted on a group of sixty patients aged 18-45 years, including forty-two women and eighteen men. After cavity preparation and isolation from saliva, tissues were highlighted with the Facelight device. The excited image was observed and evaluated with an orange filter included in the Facelight set. When the green spectrum was obtained, the restoration was placed. However, in the case of red or orange-red spectrum, the cavity preparation was continued until green light was obtained. Results. Basing on the obtained data, in thirty-one cases (51.7%) where indications of Facelight showed light-red or red colour of the bottom or cavity margins more cavity preparation was necessary. In twenty-nine patients (48.3%), in which after carious tissue preparation green colour was obtained with Facelight, twenty teeth (33.3%) were diagnosed with caries profunda and nine teeth (15%) with caries media. Conclusions. According to the research carried out on the device, the use of Facelight can improve the efficiency of carious dentine removal, in most cases without affecting the size of the cavity.